Does buyer-seller personality match enhance impulsive buying? A green marketing context - Wang, Xuhui; Tauni, Muhammad Zubair; Zhang, Qilin; Ali, Ayaz; Ali, Fayaz (Journal of marketing theory and practice, 2020)
This study investigates the effect of buyer-seller personality similarity on consumers' impulsive buying. Based on interpersonal similarity theory, the results revealed that buyer-seller similarity in agreeableness and openness increased impulsive buying of agreeable and open-minded buyers with a stronger effect of agreeable buyer-seller dyads. While neurotic buyer-seller dyads showed a significant negative effect on impulsive buying of neurotic buyers. Interestingly, conscientious and extraverted buyer-seller dyads failed to show a significant connection with the impulsive buying behavior. Thus, this study proposes that buyers exhibit different impulsive buying behavior when they interact with corresponding sellers due to their personality matching (mismatching).